Investigando a capacidade de comunicação e o consumo de bateria de PDAs em redes Bluetooth e Wi-Fi - Lopes, Roberto Rigolin Ferreira (Universidade Federal de São Carlos, 2007)
This work presents an investigation about the behavior of PDAs (Personal Digital Assistants) in wireless networks, focusing on the communication capability and battery consumption. Our hypothesis consists that hardware features of a PDA influence the communication capability and battery consumption; therefore, they are relevant in the access selection. This hypothesis is pertinent because the automatic access selection is still a challenge in the next generation of wireless networks. These networks aim the interoperability among the various technologies of access to allow users to be connected always using the best possible network environment (ABC - Always Best Connected). With the objective of verifying the hypothesis, we have developed an application called PDA Stress which, through experiments, makes the quantitative evaluation of the communication capability and battery consumption of PDAs. In our experiments, we have used two PDAs with different processing capabilities in three different networks: Bluetooth, infra-structured Wi-Fi and ad hoc Wi-Fi. The results of this work confirm the presented hypothesis. As the ABC concept is still a subject of research, we believe that the choice of the mobile device and the communication technology should be done during the project phase of an application. To help this choice, we have developed an application called PDA Chooser, which is a Decision Support System (DSS) that supports selecting an appropriate PDA and communication technology to an specific scenario. The knowledge basis of the DSS was created based on the results we collected in the case studies.
Keywords: Rede de computadores; Computação móvel; Sistemas de comunicação sem fio; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO